MONITORING AND PREDICTING THE HEMOSTATIC SYSTEM DYNAMIC CHANGES IN CASE OF DOG FEMALES’ PREGNANCY - Dubova, O. A.; Karpyuk, V. V.; Dubovyi, A. A. (Scientific Progress & Innovations, 2020)
Pregnancy of animals is accompanied by changes in all body systems to ensure optimum conditions for fetal development. Changes occur in the hemostatic system to ensure effective arrest of bleeding after child- birth. Injury of blood vessels is caused by the endotheliochorial placental type in dogs and is a starting fac- tor for the development of hemostasiopathy. Due to these patterns, a thrombophilic state develops during pregnancy, which is in an unstable equilibrium. It was found that changes in hemostasis diagram during pregnancy met the criteria of blood disseminated intravascular coagulation (DIC) syndrome and determined its latent form. Establishing thrombocytopenia in the dynamics with an increase in spontaneous aggregation of blood plates is the grounds for diagnostics and also hypofibrinogenemia, an increase in the concentration of soluble fibrin-monomer complexes and degradation products of fibrinogen/fibrin – the obvious markers of DIC syndrome. During pregnancy, the main criteria for hemostasiopathy change, so it is impossible to es- tablish the boundary between physiological and pathological changes without reference indicators. The sys- tem of monitoring and predicting dynamic changes in key indicators during dog pregnancy was tested. We used mathematical spline interpolation analysis, which enables to predict changes in indicators for a small number of key measurements: I – 20 days (embryo nidation), II – 40 days (maximum development of the pla- centa), III – 60 days (antenatal period). It was found that the changes were the most pronounced in all the parameters on the 40th day of measurements. Mathcad 15 IT-application enabled to create empirical and spline-interpolated (theoretical) graphs of changes in indicators, as well as to derive the equation of the cu- bic polynomial f(x), where x is the argument (day of measurements), f(x) – the value of the function (indica- tor). It was established that two periods were theoretically predicted in which indicator extremes were mani- fested – the 4th–12th and 48th–56th days. Mathematical equations for the dependence of dynamic changes in key indicators were calculated and they can be used to determine the reference values on a specific day of dog female pregnancy. If the values go beyond the measurement error, they indicate the development of pro- cesses that can result in increasing the intensity of DIC syndrome, which is very dangerous concerning prognostication and can threaten the life of the animal.